1988
DOI: 10.1055/s-2007-1024995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Physical Exercise on Lymphocyte Subpopulations in Trained and Untrained Subjects

Abstract: To clarify the difference in immunity between untrained subjects and well-trained athletes, the number of total leukocytes (WBC), lymphocytes, and neutrophils, percentages of various lymphocyte subpopulations (OKT3, OKT4, OKT8, Leu7, OKla1), and the levels of lymphocyte transformation response to phytohemagglutinin (PHA) were determined in five untrained male subjects and six male athletes before, immediately after, and 24 and 72 h after acute physical exercise at 60% of VO2max for 2 h. Exercise produced a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
2
2

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 10 publications
5
38
2
2
Order By: Relevance
“…The above-mentioned studies and in addition the studies by Papa et al (1989) and Oshida et al (1988) have shown that the lymphocyte proliferative response is either decreased (Papa et al 1989), elevated (Baj et al 1994;Nieman et al 1993) or in most studies unchanged (Nieman et al 1995a,b;Oshida et al 1988;Tvede et al 1991) when results are compared between trained and less trained subjects. To our knowledge no studies have demonstrated that the proliferative response to acute exercise differs between trained and untrained subjects.…”
Section: Trained Versus Nontrained Subjectsmentioning
confidence: 91%
“…The above-mentioned studies and in addition the studies by Papa et al (1989) and Oshida et al (1988) have shown that the lymphocyte proliferative response is either decreased (Papa et al 1989), elevated (Baj et al 1994;Nieman et al 1993) or in most studies unchanged (Nieman et al 1995a,b;Oshida et al 1988;Tvede et al 1991) when results are compared between trained and less trained subjects. To our knowledge no studies have demonstrated that the proliferative response to acute exercise differs between trained and untrained subjects.…”
Section: Trained Versus Nontrained Subjectsmentioning
confidence: 91%
“…The concentration of all lymphocyte subpopulations increases in the vascular compartment during exercise and decreases to levels lower than those presented in the pre-exercise period after long duration physical work 70,71 . During exercise, the CD4+ :CD8+ ratio decreases, reflecting a more remarkable increase in the TCD8+ cells in comparison to the TCD4+ 26 .…”
Section: Subpopulations Of Lymphocytesmentioning
confidence: 99%
“…subsequent to moderate or high-fit bicycle ergometer exercise [6][7][8][9], Also under these condi tions the number of total mononucleated cells increased and that of CD3+ and CD4+ cells decreased. The higher the intensity of work the greater the impact on the number of T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%